2019
DOI: 10.1016/j.annemergmed.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of the Pragmatic Airway Resuscitation Trial

Abstract: Study objective: Intubation and laryngeal tube insertion are common airway management strategies in out-of-hospital cardiac arrest. Bayesian analysis offers an alternate statistical approach to assess the results of a trial. We use Bayesian analysis to compare the effectiveness of initial laryngeal tube versus initial intubation strategies on outcomes after out-of-hospital cardiac arrest in the Pragmatic Airway Resuscitation Trial. Methods: We performed a post hoc Bayesian analysis of the Pragmatic Airway Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Likewise, the ANDROMEDA-SHOCK trial of 424 patients with severe sepsis were unable to show benefit between two targeted resuscitation strategies,18 but a Bayesian reassessment estimated a posterior probability of superiority of the peripheral-perfusion targeted strategy greater than 90% for all priors 19. The Pragmatic Airway Resuscitation Trial found that prehospital laryngeal tubes resulted in better OHCA outcomes than endotracheal intubation,20 and a post-hoc Bayesian analysis strongly affirmed the results of the parent trial 21. As demonstrated by these analyses, a Bayesian approach may better inform clinicians about intervention efficacy by combining existing evidence with new evidence to calculate an overall estimate of benefit, while also supporting future studies by estimating residual uncertainty in the evidence base for a given clinical question.…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, the ANDROMEDA-SHOCK trial of 424 patients with severe sepsis were unable to show benefit between two targeted resuscitation strategies,18 but a Bayesian reassessment estimated a posterior probability of superiority of the peripheral-perfusion targeted strategy greater than 90% for all priors 19. The Pragmatic Airway Resuscitation Trial found that prehospital laryngeal tubes resulted in better OHCA outcomes than endotracheal intubation,20 and a post-hoc Bayesian analysis strongly affirmed the results of the parent trial 21. As demonstrated by these analyses, a Bayesian approach may better inform clinicians about intervention efficacy by combining existing evidence with new evidence to calculate an overall estimate of benefit, while also supporting future studies by estimating residual uncertainty in the evidence base for a given clinical question.…”
Section: Discussionmentioning
confidence: 90%
“…Re-analysis of trial results using Bayesian statistics is becoming common in resuscitation and critical care; however to fully utilize the Bayesian methods, this should be part of the pre-planned study analysis. 49 , 50 …”
Section: Alternative Analytical Plansmentioning
confidence: 99%
“…In the Bayesian analysis of the pragmatic airway resuscitation trial, 72-hour survival and hospital survival were compared to estimate the benefit of laryngeal tube over tracheal intubation on OHCA outcomes [ 45 ]. Both under a neutral and sceptical prior distribution, better outcomes were observed with laryngeal tube than with tracheal intubation.…”
Section: Clinical Studiesmentioning
confidence: 99%